Estudo de polimorfismos no gene GRIK2 em pacientes com doença de Parkinson - BARBOSA, Suane Reis (Universidade Federal do Pará, 2018)
Parkinson's Disease (PD) is a complex neurodegenerative disorder resulting from the multiple combination of genetic and environmental factors. One of the factors that may contribute to PD development is the excitotoxicity, a pathophysiological process caused by intense stimulation of glutamatergic receptors. This neurotoxic phenomenon is associated with the excessive influx of ions in the cell (Na +, Cl- and especially Ca 2+), resulting in neuronal death. It was evidenced that the GluK2 subunit of the kainate type glutamate receptor interacts with parkin, accentuating the excitotoxic process. The GRIK2 gene encodes this subunit, expressed in regions of the brain involved in motor activity, and may undergo alternative splicing or RNA editing, introducing new isoforms that may alter the ion conductance at the receptor. There are no studies in the literature on the association of polymorphisms in the GRIK2 gene with PD. This study aimed to determine the genotypic and allelic frequencies, as well as to verify a possible influence of the SNPs rs3213607, rs2227281, rs2227283, rs2235076, rs4839797, rs2518261 from GRIK2 gene in a group of patients with PD. A case-control study was performed, with analysis of DNA samples from 129 individuals from the control group and 61 patients from the PD group. It was found that for the SNP rs2518261 (C/T), allele T appeared to have a risk effect in the DP group (x2= 19.085; p-value <0.0001; OR = 2.75; CI = 1.75-4 , 27). In this polymorphism it was also observed that TT genotype may represent a factor associated with the tremor presence in the PD group (p-value = 0.02). These pioneer results of this study, suggest that further research is needed to investigate the contribution of GRIK2 gene to PD.